Foreign Cooperation in the Japanese Government’s Fire Fighting Facilities Grant to Indonesia - Anna Bella Maharani (PT. Anagata Sembagi Education, 2024)
Cooperation is part of associative social interaction. The existence of cooperation in a group is an important element, a constructive cooperation will create successful and good results in its implementation in groups. Like group, a country needs other countries to meet its needs. This then became the trigger for foreign cooperation. The mainly focus of this research is about the cooperation between the Governments of Indonesia and Japan in International Assistance in the form of Grants for Fire Extinguishing Facilities from the Japanese Government to three Regional Governments in Indonesia, namely: Garut, Belitung, and Paniai. The importanance about this research is to explain about implementation of the Cooperation between the Governments of Japan and Indonesia in the Grant of Fire Extinguishing Facilities to the Indonesian Government, especially the Belitung Regional Government. The study show that the implementation of cooperation between the government, in this case the Belitung Regional Government and the Japanese Fire Fighting Association, has a good and mutually beneficial effect, it's just that the implementation process has not optimal yet because there are several difficulties found such as time synchronization and the involvement of several ministries which causes disparities in Standard Operating. Procedure (SOP) in its implementation. This results in the possibility that the Belitung Government cannot realize this assistance this year, because the implementation has entered the end of the fiscal year which does not allow the arrival of goods or in this case objects of assistance where the last budget disbursement process was carried out in mid-December. Based on the data research on the Cooperation between the Japanese and Indonesian Governments in Fire Fighting Facilities Grants associated with the concept of good governance, the author's suggestion regarding this research is that hoped in the future the Indonesian government will further improve the quality of its bureaucracy by applying values to the concept of good governance so that problems and difficulties such as those encountered in the implementation of the Cooperation between the Japanese and Indonesian Governments in the Fire Fighting Equipment Grant can be minimized.